Complex flexibility of the transforming growth factor beta superfamily. - Venkataraman, G (1995)
The transforming growth factors beta (TGF-beta s) are important modulators of growth and differentiation. They are intermolecular disulfide-bonded homodimeric molecules. The monomer fold has a conserved cystine knot and lacks a hydrophobic core. The biological specificity of a given member of the family is believed to be determined by the conformational flexibility of the variable loop regions of the monomer. The monomer subunit assembly in the dimer is stabilized mainly by hydrophobic contacts and a few hydrogen bonds. Since these interactions are nondirectional, we examined subunit assemblies of TGF-beta by using conformational analysis. The different subunit assemblies in TGF-beta 2 dimer were characterized in terms of the intersubunit disulfide torsion. Our analyses show that the subunit assemblies fall into two states: the crystallographically observed gauche+conformation and the previously not reported gauche--conformation, both having almost identical interaction energies. Furthermore, there is significant flexibility in the subunit assembly within the gauche+ and the gauche- states of the disulfide bond. The monomer subunit assembly is independent of the variations about the loop regions. The variations in the loop regions, coupled with flexibility in the monomer assembly, lead to a complex flexibility in the dimer of the TGF-beta superfamily. For the TGF-beta superfamily, the cystine knot acts as a scaffold and complex flexibility provides for biological selectivity. Complex flexibility might provide an explanation for the diverse range of biological activities that these important molecules display.